Learners’ Diary In The Implementation of Project - Based Learning Strategy In English Instructional Technology Class - Novita Eka Tristiana; Rudi Hartono; Abdurrachman Faridi; Sri Wuli Fitriati (Universitas Negeri Semarang, 2023)
Learners ‘diary used to build good relationship and communication between lecturer and students on the implementation of Project-Based Learning Strategy in teaching English Instructional Technology Class. This research aims to describe about the students experience in the implementation of Project-Based Learning Strategy in teaching English Instructional Technology through learners’ diary. The descriptive qualitative is used in this research. The data collecting techniques used are learners ‘diary, observation, and interview. The participants of the research are ten pre-service teachers who take English instructional technology class in English department at one of the University in Pringsewu Lampung. The result of the study shows that the pre-service teachers know about the project topic and want to know more about the topic in implementing the project. Moreover, pre-service teachers also encounter some problems in doing the project, but they have tried to solve their problems by group discussion. Learners’ diary is important to be used in implementing project-based learning to control the students in doing the project and as the communication media for the pre-service teachers to share their experience and activities in doing the project.